UPLC-MS/MS Technology for the Quantitative Methodology and Pharmacokinetic Analysis of Voxtalisib in Rat Plasma - Li, Qingqing; Liu, Ya-nan; Wang, Jing; Hu, Yingying; Hu, Jinyu; Xu, Ren-ai; Shao, Liu; Chen, Lianguo (Frontiers in Pharmacology, 2022)
Voxtalisib, is a specific, effective, and reversible dual inhibitor, which inhibits both pan-class I phosphoinositide 3-kinase (PI3K) and mechanistic target of rapamycin (mTOR). To date, voxtalisib has been studied in trials for melanoma, lymphoma, glioblastoma, breast cancer, and other cancers. In this study, a highly sensitive and rapid ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) technology was applied to the quantitative methodology and pharmacokinetic analysis of voxtalisib in rat plasma. After protein precipitation of the analyte by acetonitrile, the chromatographic separation was performed by gradient elution on an Acquity BEH C18 column (2.1 mm × 50 mm, 1.7 μm) with acetonitrile (solvent A) and 0.1% formic acid (solvent B) as the mobile phase. In the positive ion mode, the mass transfer detection of the analyte and IS was m/z 270.91 > 242.98 and m/z 572.30 > 246.10, respectively. In the concentration range of 1–2000 ng/ml, a good linear relationship of voxtalisib was successfully established by the UPLC-MS/MS technology, and the lower limit of quantification (LLOQ) of the analyte was identified as 1 ng/ml. Intra-day and inter-day precisions for voxtalisib were 7.5–18.7% and 13.0–16.6%, respectively, and the accuracies were in the ranges of −14.0–2.0% and −7.2–3.1%, respectively. The matrix effect, extraction recovery, carryover and stability of the analyte were all in compliance with the acceptance criteria of bioassays recommended by FDA. Finally, the pharmacokinetic profile of the analyte had been availably studied by the UPLC-MS/MS bio-analytical method after rats were treated by intragastric administration with voxtalisib (5 mg/kg). The results indicated that the UPLC-MS/MS technology can effectively and quickly quantify the analyte, and this method can also be used for the pharmacokinetic study of voxtalisib, which can provide reference for the optimization of clinical drug management in the later period.